1973
DOI: 10.1128/jb.116.3.1267-1272.1973
|View full text |Cite
|
Sign up to set email alerts
|

Production of Volatile Nitrogenous Compounds from the Degradation of Streptomycin by Pseudomonas maltophilia

Abstract: Ammonia, methylamine, and pyridine were detected in broth filtrates of a streptomycin-degrading strain of Pseudomonas maltophilia during growth on streptomycin as a sole carbon and nitrogen source. Ammonia and methylamine, quantitatively measured by conversion to chromophores with picryl sulfonic acid, were found to accumulate in broth, whereas pyridine concentration increased in the early stages of streptomycin degradation and then decreased as the degradation of the antibiotic neared completion. Exogenous py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…If drying is incomplete, the equipment may become contaminated with S. maltophilia, particularly since the organism is known to adhere to plastics (19). It is not known if S. maltophilia would be capable of surviving exposure to the extremely high concentrations of tobramycin that occur in this setting, but it is interesting to note that a strain of S. maltophilia has been reported that utilized streptomycin as an energy source (13). Further studies would be needed to assess the level of contamination of nebulizers with S. maltophilia.…”
Section: Discussionmentioning
confidence: 99%
“…If drying is incomplete, the equipment may become contaminated with S. maltophilia, particularly since the organism is known to adhere to plastics (19). It is not known if S. maltophilia would be capable of surviving exposure to the extremely high concentrations of tobramycin that occur in this setting, but it is interesting to note that a strain of S. maltophilia has been reported that utilized streptomycin as an energy source (13). Further studies would be needed to assess the level of contamination of nebulizers with S. maltophilia.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterium has been regarded as relatively metabolically inactive (395), but a variety of unusual substrates, including the aminoglycoside antibiotic streptomycin (127), may be metabolized (37,39,55,191,209,244,273,291,333,398) and strains of the bacterium have been investigated for their potential use as biodegradative agents. Selected biochemical characteristics and microbiological reactions of S. maltophilia are shown in Table 1.…”
Section: Biochemical Characteristicsmentioning
confidence: 99%
“…It has been isolated from a number of water sources including rivers, wells, a hypereutrophic lake, and bottled water (in which it may be responsible for altered organoleptic properties), and sewage (13,167,176,183,184,185,219,288,319). The bacterium has also been recovered from a variety of soil (44,85,127,400) and plant rhizosphere environments, including grasses, sugarcane and palms (202), from wheat (203), cabbage, rape, mustard, corn (86), beet (86,243), bananas, cotton, beans, tobacco (183), rice paddies (235), citrus plants (1), orchids (447), irises (25), legume inoculants which use nonsterile peat as a carrier (306), and stored timber (108). Iizuka and Komagata reported the isolation of S. maltophilia from oil brines and other related materials from oil fields in Japan (191).…”
Section: Geneticsmentioning
confidence: 99%
“…Previous studies showed that the phytotoxicity of antibiotics on plants in the soil varies between plant species and antibiotic compounds, and antibiotics could have a biphasic effect on plant growth characterized by low-dose stimulation and high-dose inhibition, which is also called hormesis. Thus, oxytetracycline might also induce hormesis in radish plants, but streptomycin did not. In this study, although the continuous soil drenching was conducted for 74 days, the low bioavailabilities of both antibiotics in soil due to the strong adsorption on soil components and rapid degradations might be the reason for no inhibition effect on plant growth.…”
Section: Resultsmentioning
confidence: 98%